Using the webquest model as alternative assessment in the course LM-1001 Integrated English I at the University of Costa Rica - Navas Brenes, César Alberto (Universidad de Costa Rica, 2013)
This article explores the pedagogical principles as well as the advantages and recommendations of designing and implementing WebQuests in the course LM-1001 Integrated English I in the School of Modern Languages at the University of Costa Rica. This type of Web-based task was used as alternative assessment rather than traditional evaluation. This study also presents three sample WebQuests which were implemented with four groups in four different semesters of first-year students during their computer lab sessions.